2021
DOI: 10.3390/nano11051146
|View full text |Cite
|
Sign up to set email alerts
|

Blend Structure and n-Type Thermoelectric Performance of PA6/SAN and PA6/PMMA Blends Filled with Singlewalled Carbon Nanotubes

Abstract: The present study investigates how the formation of melt-mixed immiscible blends based on PA6/SAN and PA6/PMMA filled with single walled nanotubes (SWCNTs) affects the thermoelectric (TE) properties. In addition to the detailed investigation of the blend morphology with compositions between 100/0 wt.% and 50/50 wt.%, the thermoelectric properties are investigated on blends with different SWCNT concentrations (0.25–3.0 wt.%). Both PA6 and the blend composites with the used type of SWCNTs showed negative Seebeck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…The light microscopic images of the composites show many large elongated remaining SWCNT agglomerates ( Figure 5 and Figure 10 ). This poor dispersibility of the SWCNT Tuball™ material has been reported before and was found to also be typical in PP [ 15 , 31 ], acrylonitrile butadiene styrene (ABS) [ 32 ], and polyamide 6 [ 32 , 33 ]-based composites. From the SEM study, it was concluded that PC and PEG are miscible in the solid state, in which the measurements were performed, but PBT and PEEK are not.…”
Section: Discussionsupporting
confidence: 51%
“…The light microscopic images of the composites show many large elongated remaining SWCNT agglomerates ( Figure 5 and Figure 10 ). This poor dispersibility of the SWCNT Tuball™ material has been reported before and was found to also be typical in PP [ 15 , 31 ], acrylonitrile butadiene styrene (ABS) [ 32 ], and polyamide 6 [ 32 , 33 ]-based composites. From the SEM study, it was concluded that PC and PEG are miscible in the solid state, in which the measurements were performed, but PBT and PEEK are not.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, the potential candidates for low-operating-temperature TE materials are only laboratory technologies at present, and large-scale, low-cost preparation technologies need to be explored further. Very recently, research on graphene, single-walled carbon nanotubes (SWCNTs), and TE material nanocomposites demonstrated better ZT performance, as well as improved electrical conductivity (σ) and were successful in suppressing the thermal conductivity, κ [ 27 , 165 , 166 , 167 ]. The κ of TE nanocomposites is predicted to be lower than that of their bulk equivalents of the same chemical configuration.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Very recently, research on graphene, single-walled carbon nanotubes (SWCNTs), and TE material nanocomposites demonstrated better ZT performance, as well as improved electrical conductivity (σ) and were successful in suppressing the thermal conductivity, κ [ 27 , 165 , 166 , 167 ]. The κ of TE nanocomposites is predicted to be lower than that of their bulk equivalents of the same chemical configuration.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…These conducting polymers exhibit light weight, lower cost, reasonable thermal conductivity, easy fabrication process, and excellent flexibility. For instance, the thermoelectric performance of organic polymers can be significantly improved by controlling the combination of carbon nanotubes (CNTs) or graphene nanosheets with such polymers [ 1 , 2 , 3 ]. So far, the most common conducting polymers that have been investigated as thermoelectric materials are polyaniline (PANI) [ 4 ], polypyrrole (PPy) [ 5 ], and poly (3,4-ethylene dioxythiophene) (PEDOT) [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%